Mathematics Problem Solving Ability in Terms of Adversity Quotient in Problem Based Learning Model With Peer Feedback (Unnes Journal of Mathematics Education Research, 2020)
This study aimed to describe the ability of students' problem-solving based on adversity quotient. This study is a mixed-method with sequential explanatory design. The subject of the study is the 8th-grade students of SMP Negeri 1 Miomaffo Timur in the school year of 2018/2019 with class VIII A as the experimental class subject to problem-based learning models with peer feedback and class VIII B as the control class subject to discovery learning models. Quantitative data collection was obtained from the test results of the problem-solving ability of material flat side geometry and qualitative data collection was done by interviewing the results of the problem-solving ability tests through a model of problem-based learning with peer feedback. The result revealed that learning model problem based learning with effective peer feedback and a description of problem-solving abilities in terms of adversity quotient in the high, medium and low categories of the problem-based learning model with peer feedback had various results. It is shown from 4 quitter students, there was no high problem-solving ability, 2 students at no medium problem-solving ability and 2 students at low problem-solving ability. From 15 camper students, 6 students have high problem-solving abilities, 7 students have medium problem-solving abilities, and 2 students who have low problem-solving abilities. From 13 climber students, 5 students had high problem-solving abilities, 7 students had medium problem-solving abilities, and 1 student who had low problem-solving abilities.